Postcard of Murska Sobota (50) - Jože Kološa (Wikimedia Commons, 1950)
Notice image issue de Wikimedia Commons. Titre: Postcard of Murska Sobota (50). Postcard of Murska Sobota.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; architecture; Histoire Locale